Hubungan Pengetahuan Siswi dengan Minat dalam Pemilihan Pembalut Kain - Ayu Puspita; Septian Mugi Rahayu; Amelia Excoelsa (Jurnal Surya Medika (JSM), 2021)
Sanitary napkins during menstruation are the main requirement. According to research, disposable sanitary napkins currently used are carcinogenic and contain harmful substances that can cause dangerous diseases for the reproductive organs. The general objective of this study was to determine the relationship between student knowledge and interest in the selection of cloth sanitary napkins. The design of this study used a literature review design. Articles are collected using search engines such as EBSCO, Sciencedirect, Proquest, and Google Scholar. The criteria for the articles used were those published in 2019 and 2020. Based on the articles collected, it was found that there was a relationship between knowledge and interest. According to the researchers, this happened because these three studies had the same subject characteristics. The research respondents were women who had experienced menstruation and the similarity of research in choosing the right and safe, sanitary napkins for women's reproductive health. A woman is expected to be able to choose the right sanitary napkin. Mistakes in choosing pads can result in skin irritation, allergies, skin diseases, and infections. The choice of sanitary napkins is also adjusted to the activities a woman will do.